Analysis of an alternative actuator for primary control surfaces - Zare Shahneh, Amir; Pandirolla, Shiva Kumar Vutla (MedCrave Group, 2022)
Aviation Industry has adverse effects on the environment since past few years. Despite these effects, industry is expected to grow more than 10% strategically in many regions across the globe in a near future. Accordingly, several global aerospace Original Equipment Manufacturers (OEM) and Research organisations are focusing on this trend to develop eco-friendly aircraft which aim to use the renewable sources of energy. Output of that research is to Design, Develop, Manufacture and Qualify the All-Electric Aircraft (AEA) and release into the market within the near future. When it comes to the electrification of the aircraft, every single conventional system on the aircraft is driven using electric energy rather than hydraulics or pneumatics. Control surfaces and other secondary systems on the conventional aircraft operates using hydraulic or pneumatic driven actuators and they have direct or indirect effect on the environment. To begin with, this research has mainly focused on design and development of Jam-Tolerant Electromechanical or ElectroMechanical Actuator (EMA) concepts.
Keywords: aviation industry; alternative actuators; primary control surfaces; jam tolerant/anti jam EMA